Role of Bioactive Constituents of Panax notoginseng in the Modulation of Tumorigenesis: A Potential Review for the Treatment of Cancer - Tan, Ming-Ming; Chen, Min-Hua; Han, Fang; Wang, Jun-Wei; Tu, Yue-Xing (Frontiers in Pharmacology, 2021)
Cancer is the leading cause of death, affecting people in both developed and developing countries. Cancer is a challenging disease due to its complicated pathophysiological mechanisms. Many anticancer drugs are used to treatment cancer and reduce mortality rates but their toxicity limits their administration. Drugs made from natural products with multi-targeted therapy have the ability to target critical signalling proteins in different pathways. Natural compounds have pharmacological activities such as anticancer activity, low toxicity and minimum side-effects. Panax notoginseng is a medicinal plant whose extracts and phytochemicals are used to treatment of cancer, cardiovascular disorders, blood stasis, easing inflammation, edoema, and pain. P. notoginseng's secondary metabolites target cancer's dysregulated pathways, causing cancer cells death. In this review, we focused on several ginsenosides extracted from P. notoginseng that were evaluated against various cancer cell lines for cancer treatment. Furthermore, an in vivo investigation of these ginsenosides should be conducted to gain insight into the dysregulation of several pathways, followed by clinical trials for the potential and effective treatment of cancer.